2021
DOI: 10.3390/app112210848
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization in Open-Pit Mining: A New Approach in Monitoring and Control of Rock Fragmentation

Abstract: Mining enterprises are widely introducing digital technologies and automation is one of such tools. Granularity monitoring, namely, the size determination of rock mass pieces is a common operational component of the processes that extract minerals by open-pit mining. The article proposes an approach that, in addition to the lump size distribution, makes it possible to estimate the lump form distribution as well. To investigate the effectiveness of monitoring the form of blasted rock mass lumps, the authors con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…One of the main conditions for the implementation of the first strategy is the availability of a sufficient level of technological, scientific, and technical potentials [4][5][6][7][8][9][10][11][12][13][14]. At the same time, the decline in the quality, consumer, and functional characteristics of industrial goods complicate the continuous updating of technologies due to the growth strategy and form the need to focus on the strategy of innovation-distribution differentiation based on the stratification of industries in the industrial sector, taking into account the level of technological potential and the level of capacity utilization [15], which The increased technological potential ensures the production of competitive industrial products in the process of its use [16,17]. To determine the parametric characteristics of the processes of development of technological potential, the method of econophysics (the method of analogy in the model of mechanical movement of the body) was applied, which makes it possible to consider the branch of the industrial sector as a certain object with a certain mass, speed, and position in the process of technological development.…”
Section: The Power Consumption Analysismentioning
confidence: 99%
“…One of the main conditions for the implementation of the first strategy is the availability of a sufficient level of technological, scientific, and technical potentials [4][5][6][7][8][9][10][11][12][13][14]. At the same time, the decline in the quality, consumer, and functional characteristics of industrial goods complicate the continuous updating of technologies due to the growth strategy and form the need to focus on the strategy of innovation-distribution differentiation based on the stratification of industries in the industrial sector, taking into account the level of technological potential and the level of capacity utilization [15], which The increased technological potential ensures the production of competitive industrial products in the process of its use [16,17]. To determine the parametric characteristics of the processes of development of technological potential, the method of econophysics (the method of analogy in the model of mechanical movement of the body) was applied, which makes it possible to consider the branch of the industrial sector as a certain object with a certain mass, speed, and position in the process of technological development.…”
Section: The Power Consumption Analysismentioning
confidence: 99%
“…The mineral and raw material complex plays a leading role in Russia's economy, as a factor in its steady development. It is no wonder that mining and processing companies are the largest consumers of electricity [2]. More than 3 billion tonnes of raw materials are crushed every year.…”
Section: Introductionmentioning
confidence: 99%
“…Counteraction to this cannot occur due to isolation, since the energy sector is not able to exist for a long time in isolation from other spheres and external influence [38,39]. As a response to challenges, end-to-end digital technologies and Industry 4.0 technologies are developing [40][41][42][43][44], stimulating the restructuring of the energy sector [45]. Authors have identified seven blocks of technologies, united by common functions or ways of realization: digital and IT, smart grid, renewable and Non-conventional energy sources, storage technologies, and a block of industrial production technologies [46,47].…”
Section: Introductionmentioning
confidence: 99%